2009
DOI: 10.1038/sj.bjc.6604880
|View full text |Cite
|
Sign up to set email alerts
|

Non-steroidal anti-inflammatory drugs and risk of gastric and oesophageal adenocarcinomas: results from a cohort study and a meta-analysis

Abstract: Use of aspirin or other non-steroidal anti-inflammatory drugs (NSAIDs) may reduce the risk of gastric or oesophageal adenocarcinomas. We examined the association between self-reported use of aspirin or non-aspirin NSAIDs in the earlier 12 months and gastric non-cardia (N ¼ 182), gastric cardia (N ¼ 178), and oesophageal adenocarcinomas (N ¼ 228) in a prospective cohort (N ¼ 311 115) followed for 7 years. Hazard ratios (HRs) and 95% confidence intervals (CIs) come from Cox models adjusted for potential confound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
154
1
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(173 citation statements)
references
References 42 publications
13
154
1
5
Order By: Relevance
“…(Jemal et al, 2007) It is therefore important to identify aetiological and protective factors for this disease to improve primary prevention. Non-steroidal anti-inflammatory drugs (NSAIDs), especially aspirin, have been reported to reduce the risk of several cancers and some pre-malignant lesions, with risk reductions ranging from 20% to 50% for certain cancer sites (Garcia- Rodriguez and HuertaAlvarez, 2001;Khuder and Mutgi, 2001;Gonzalez-Perez et al, 2003;Abnet et al, 2009;Cole et al, 2009).…”
mentioning
confidence: 99%
“…(Jemal et al, 2007) It is therefore important to identify aetiological and protective factors for this disease to improve primary prevention. Non-steroidal anti-inflammatory drugs (NSAIDs), especially aspirin, have been reported to reduce the risk of several cancers and some pre-malignant lesions, with risk reductions ranging from 20% to 50% for certain cancer sites (Garcia- Rodriguez and HuertaAlvarez, 2001;Khuder and Mutgi, 2001;Gonzalez-Perez et al, 2003;Abnet et al, 2009;Cole et al, 2009).…”
mentioning
confidence: 99%
“…Previous case-control and epidemiologic cohort studies have demonstrated that the orderly use of non-steroidal anti-inflammatory drugs decreased digestive tract malignancy mortalities, including colorectal and gastric adenocarcinoma (14,15). Consequently, the COX-2 enzyme is considered a potential therapeutic marker for the prevention and treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it cannot differentiate whether any beneficial effect of NSAID use is produced before or after BE appearance. In 2009, a questionnaire based study that included approximately 300000 members of the American Association of Retired Persons found no significant association between EAC and the use of aspirin or non-aspirin NSAIDs [36] . Since 2003, several observational studies comparing BE and EAC patients have been published (Table 1).…”
Section: Nsaids and Eac Chemopreventionmentioning
confidence: 99%
“…Nevertheless, the attributable risk is small (12 per 100000 person-years) and no change in cognitive function was found in randomized trials of statins in elderly patients [130] . Because BE patients are usually old with various multi-systemic comorbidities [36] , increased toxicity is expected [133] with statin use. No study today has specifically addressed statin toxicity in BE patients.…”
Section: Side Effects Of Statin Chemopreventionmentioning
confidence: 99%